(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article explores the critical role of gender audits in eradicating harassment and ensuring its prevention in the workplace in Uzbekistan. By examining the legal frameworks, methodologies, and outcomes associated with gender audits, the study highlights the significance of these audits as comprehensive tools for identifying, understanding, and addressing gender imbalances and discrimination in organizational settings. Through detailed analysis of policies, practices, and procedures, gender audits facilitate the development of targeted interventions aimed at promoting gender equality and safeguarding against harassment. The findings emphasize the importance of gender audits in fostering a culture of respect and equality, detailing the processes involved in conducting audits, and the impactful outcomes that can be achieved. The article further discusses the legislative context in Uzbekistan that supports gender audits, including specific laws and codes that frame the country’s approach to gender equality and protection against harassment. By showcasing the effectiveness of gender audits in driving organizational change and enhancing workplace culture, the article advocates for their broader adoption and implementation as a key strategy in combating workplace harassment.